Engaging local youths in humanitarian response is not a matter of if but how - Apollo, Abigael; Mbah, Marcellus Forh (Journal of International Humanitarian Action, 2022)
Abstract Despite being critical responders in humanitarian crises, local youths are continually left out of the humanitarian action agenda. This paper used a qualitative methodology to investigate local youths’ role in humanitarian response and their impacts and assessed how humanitarian actors influence the effectiveness of youth engagement. The data was collected through semi-structured interviews with local youths who participated in the Ebola response in Sierra Leone. Findings showed that young people are significantly contributing to crises response. However, they lack an enabling environment and support system to convert their skills into valuable humanitarian resources efficiently. Therefore, despite the rhetoric that many reports and policies reflect, this study establishes that the realities of youth engagement in humanitarian activities are often misunderstood and controlled for the self-interest of different actors other than youths themselves. It advocates for a renewed focus and support for young people’s skills as paramount for effective humanitarian response and building back resilient communities after emergencies. Besides, engaging local youths in tackling crises empowers them with transferable skills and stimulates their passion for participating in development issues within their communities.
KerkoCite.ItemAlsoKnownAs: 10.1186/s41018-022-00118-x 5072953:G7EVXRD4 openalex: W4226148211
Keywords: C:Sierra Leone; _z:class:countries; _z:class:themes; oa:keyword:humanitarian response; oa:keyword:local youths; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T11556 Impact of Child Labor Interventions; oa:topic:T11581 Ebola Virus Research and Outbreaks; openalex:n:1; openalex:yes

Engaging local youths in humanitarian response is not a matter of if but how - Apollo, Abigael; Mbah, Marcellus Forh (Journal of International Humanitarian Action, 2022)
Abstract Despite being critical responders in humanitarian crises, local youths are continually left out of the humanitarian action agenda. This paper used a qualitative methodology to investigate local youths’ role in humanitarian response and their impacts and assessed how humanitarian actors influence the effectiveness of youth engagement. The data was collected through semi-structured interviews with local youths who participated in the Ebola response in Sierra Leone. Findings showed that young people are significantly contributing to crises response. However, they lack an enabling environment and support system to convert their skills into valuable humanitarian resources efficiently. Therefore, despite the rhetoric that many reports and policies reflect, this study establishes that the realities of youth engagement in humanitarian activities are often misunderstood and controlled for the self-interest of different actors other than youths themselves. It advocates for a renewed focus and support for young people’s skills as paramount for effective humanitarian response and building back resilient communities after emergencies. Besides, engaging local youths in tackling crises empowers them with transferable skills and stimulates their passion for participating in development issues within their communities.
KerkoCite.ItemAlsoKnownAs: 10.1186/s41018-022-00118-x 5072953:G7EVXRD4 openalex: W4226148211
Keywords: _z:class:countries; _z:class:themes; oa:keyword:humanitarian response; oa:keyword:local youths; oa:topic:T10747 Community Resilience to Natural Disasters; oa:topic:T11556 Impact of Child Labor Interventions; oa:topic:T11581 Ebola Virus Research and Outbreaks; openalex:n:1; openalex:yes

Towards an Integrated Approach to Climate Change Education in Tanzania: The Role of Indigenous Knowledge Systems - Mugabe, Paschal Arsein; Mbah, Marcellus; Apollo, Abigael; Mbah, Marcellus F. (Indigenous Methodologies, Research and Practices for Sustainable Development, 2022)
There have been many efforts globally toward fighting climate change; including international agreements, conferences, research, policies, forums, etc. In addition to these efforts, climate change education has recently emerged as an essential capacity-building tool to curb the climate crisis. However, development practitioners from the Global South have cited limitations with climate change education due to the dominance of Eurocentric epistemologies over indigenous knowledge (IK) approaches. This study therefore advocates for the integration of indigenous knowledge into climate change education in Tanzania for achieving a sustainable environment. Seventy documents, including peer-reviewed papers, reports from corporate institutions, policy briefs, proceedings and other grey literature were reviewed. We establish that IK systems are not integrated into CCE in Tanzania. However, we find opportunities for integration due to the evidence of the existing CCE efforts and potential complementary indigenous practices. By identifying, documenting, and validating indigenous knowledge and merging this knowledge with scientific insights, the fostering of an integrated approach to combat the enduring effects of climate change can be evidenced.
openalex:W4312587358 mag: KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-12326-9_16 5072953:7MNR46WW 5072953:F3ACIBMT
Keywords: C:Tanzania; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:climate change education; oa:keyword:indigenous knowledge systems; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T12656 Impact of Climate Change on Human Migration; oa:topic:T13839 Volunteer Tourism and Global Development Impacts; openalex:import; openalex:n:1; openalex:yes